Sensory evaluation of two new biofortified bean varieties in Guatemala and Honduras - Gallego, Sonia; Reyes, Byron A. (2023)
For several years, the bean breeding and biofortification programs at the Alliance Bioversity - CIAT have worked with the Instituto de Ciencia y Tecnologías Agrícolas (ICTA) in Guatemala and the Escuela Agrícola Panamericana, Zamorano, and the Dirección de Ciencia y Tecnología Agropecuaria (DICTA) in Honduras, in evaluating different bean lines with the goal of releasing biofortified varieties with higher iron and zinc content, that could be produced, commercialized and consumed by producing families and consumers in general, in the dry corridor of Central America. Under the PASA (Novel climate resilient common bean cultivars for food security in Honduras and Guatemala) project, we conducted sensory test for biofortified beans in Guatemala y Honduras, to determine the acceptability of these materials by consumers, prior to their official release, comparing this to biofortified varieties in the market, and a control variety. The results suggest that the new biofortified varieties have high acceptability, but require marketing strategies that highlight their nutritional benefits, so consumers are aware about this. Further, in Honduras, additional efforts are required to promote the production and consumption of the new biofortified variety, as it scored slightly lower in terms of cooked grain color. This poster summarizes these results.